Mathematical Model of Zakat and Low-Tax Policy Effects on Economic Population - Muhammad Subhan; Riry Sriningsih (UIN Sumatera Utara, 2026)
Many Islamic countries implement low-tax policies, but these often fail to reduce inequality and poverty. Zakat has a function to redistribute wealth, but previous studies fail to explore its dynamic interaction with tax systems. This study builds a mathematical model that describes the combined effects of zakat and low-tax policies on economic population dynamics. We develop a system of differential equations that represents wealthy, middle, and poor populations, then analyze it qualitatively by finding equilibrium points and their stability. Analysis reveals a single asymptotically stable equilibrium point, indicating that zakat effectively reduces the wealth gap, even under a low-tax setting. We also established a threshold condition for the middle-to-poor population ratio, guiding policymakers on designing effective poverty interventions. This study lays a theoretical groundwork that incorporates Islamic financial institutions into poverty reduction strategies.